Progettare un laboratorio di scrittura italiana all’università. Un modello centrato sull’approccio per temi e per problemi - Sposetti, Patrizia (Incontri. Rivista europea di studi italiani, 2017)
Designing an academic Italian writing lab A ‘topics & problems’ approachThe purpose of this paper is to present a specific model of plane writing laboratories for Italian university students. Academic writing competencies have a central position in the educational path, so the writing skills of university students are a matter of increasing interest at the international level. In the Italian context it is also an important topic of scientific debate, as research, study and institutional and regulatory frameworks show. Specifically, this paper describes the educational experience of plane writing courses started in 2000 in the Department of Philological, Linguistic and Literary Studies (formerly Faculty of Humanities) at the Sapienza University of Rome. The theoretical starting points are an awareness of the teachability of writing and – therefore – the importance of educational work. The approaches, methods and integrated practice activities presented in this paper assume that writing involves the following skills: language skills (mastery of writing tools, mastery of morphosyntax, mastery of lexical and semantic levels of speech); textual skills (ability to organize a text, ability to structure and organize ideas); cognitive skills (ability to develop, select and combine information); pragmatic skills (ability to deliver a consistent message within a communicative situation); and metacognitive skills (ability to decentralize oneself from the text in order to submit it for review and evaluation of its acceptability and consistency). Therefore essential objectives are that students learn to be able to select, organize and formulate their own ideas on the basis of a specific communicative situation, in which the context, purposes and recipient are clearly defined.